Temporary loss of consciousness during cetuximab treatment of a patient with metastatic colon cancer: a case report - Taro Fukui; Koichi Suzuki; Sawako Tamaki; Iku Abe; Yuhei Endo; Hideki Ishikawa; Nao Kakizawa; Fumiaki Watanabe; Masaaki Saito; Shingo Tsujinaka; Kazushige Futsuhara; Yasuyuki Miyakura; et al. (Surgical Case Reports, 2019)
Abstract Background Anti-epidermal growth factor receptor (EGFR) antibody is widely used for the treatment of patients with metastatic colorectal cancer. Hypomagnesemia is a comparatively frequent adverse event of this drug, which is likely overlooked because it occurs later in treatment without symptoms. Furthermore, hypomagnesemia and hypomagnesemia-induced corrected QT (QTc) prolongation may lead to loss of consciousness (LOC), the onset of which is not generally considered associated with the treatment of anti-EGFR antibody because of its rare occurrence. Here, we present a colorectal cancer patient treated with anti-EGFR antibody, who suffered LOC during treatment while severe hypomagnesemia or QTc prolongation was not observed. Case presentation A 69-year-old man with metastatic colon cancer was treated with cetuximab (anti-EGFR antibody) plus irinotecan as third-line chemotherapy. His serum magnesium level gradually decreased, and grade 2 hypomagnesemia (a serum magnesium level of 0.9 mg/dL) was observed at the 12th administration of cetuximab. In light of this development, intravenous supplementation of 20 mEq magnesium sulfate began with careful blood monitoring despite the lack of clinical symptoms. Electrocardiogram (ECG) showed prolonged QT or corrected QT (QTc) intervals (grade 1). His serum magnesium level remained at 0.9 mg/dL, and no hypomagnesemia symptoms were observed by the 17th administration of cetuximab. After the treatment, however, he suddenly lost consciousness without symptoms related to infusion or allergic reactions. Circulatory collapse following dermatological reactions and respiratory events were not evident. Intravenous supplementation of magnesium sulfate was administered again. He awakened 2 min after the onset of temporary LOC without any other symptoms related to hypomagnesemia, such as lethargy, tremor, tetany, and seizures. No other etiology outside of the low level of serum magnesium was confirmed in further examinations. Cetuximab was discontinued, and his serum magnesium level returned to a level within the normal range after 6 weeks. Because of tumor progression, regorafenib and TAS-102 (trifluridine tipiracil hydrochloride) were introduced sequentially for 6 months. Five months after the final treatment of TAS-102, he died of his primary disease, which reflected a survival period of 4 years and 6 months since the beginning of treatment. Conclusions This case report reminds clinicians that LOC can be induced without severe hypomagnesemia or QTc prolongation, during anti-EGFR antibody treatment for metastatic colorectal cancer even while under carefully monitored magnesium supplementation.